Moderating role of accounting knowledge and education level on UTAUT2 model in MSMEs - Gilda, Vanessa; Putra, Robiur Rahmat (Politeknik Ganesha Medan, 2024)
This study aims to examine and analyze the influence of the UTAUT2 factor on interest in using accounting software with accounting understanding and level of education as moderating variables. The population in this study used a sample of 377 respondents who are MSME owners in the DKI Jakarta area. The data collection technique used simple random sampling by distributing research questionnaires in the form of google forms via social media according to the researcher's criteria. The data processing method in this study uses the SmartPLS software which is used to test the hypothesis. The results of this study indicate that performance expectations, effort expectations, hedonic motivation, social influence, and understanding of accounting have a positive and significant effect on interest in using accounting software. Accounting knowledge cannot moderate the effect of effort expectations on interest in using accounting software. The level of education is able to moderate the effect of performance expectations, business expectations, and social influences on interest in using accounting software. This study recommends to MSME owners that the use of accounting applications encourages the use of accounting data, because accounting applications automatically, accurately, and authentically provide the accounting data needed by MSMEs in managing their business finances.